Coupling anodic and cathodic reactions using an electrocatalytic dual-membrane system actuates ultra-efficient degradation with regulable mechanisms. (15th April 2023) - Gao, Yifan; Liang, Shuai; Zhang, Quanbiao; Wang, Kunpeng; Liang, Peng; Huang, Xia
Highlights: Coupling anodic and cathodic reactions enables regulable reaction mechanisms. Appropriate coupling strategy actuates ultra-efficient electrocatalytic degradation. Systematic tests unravel complex interaction between anode and cathode reactions. Flexible tuning of direct and indirect oxidation meets versatile degradation need. Abstract: The versatile reaction possibilities arising from the interaction between the anodic and cathodic reactions naturally contained in electrocatalytic membrane filtration (EMF) systems are of great valuable in meeting the current complex water treatment requirements. But currently, most studies only focus on half-cell reactions with a single electrocatalytic membrane, which limits the research progress of the EMF technology. Here we report a coupling strategy that utilizes the interaction between the anodic and cathodic reactions to actuate ultra-efficient degradation performance with regulable reaction mechanisms. An electrocatalytic dual-membrane filtration (EDMF) system was established. Six typical configurations of the EDMF system were set up and systematically investigated by adjusting the electrode distance and filtration sequence. Based on the obtained results of degradation performance and mechanisms, a regulation strategy which enabled flexible tuning of direct nonradical oxidation (e.g., h + ) and indirect oxidation (e.g., 1 O2, ·OH, HO2 ·, O2 · −, etc.) was proposed. In particular, cathodic reactions were found to adversely affect the anodic reactions at the relatively short electrode distance of 0.9 mm. Anodic reactions could inhibit the generation of 1 O2 at short distance of 0.9 mm but promote its generation at long distances of 9 and 17 mm. The A–C_0.9 configuration achieved the highest degradation performance, while the C–A_9 configuration was revealed to be much more conducive to 1 O2 production. Overall, our findings demonstrate the versatility and tunability of the reaction mechanism and performance of the EDMF system due to the flexible coupling of the anodic and cathodic reactions, which potentially lays a foundation for future development of ultra-efficient mechanism-adjustable electrocatalysis technologies. Graphical abstract: Image, graphical abstract